Critical Interaction Between Telomerase and Autophagy in Mediating Flow-Induced Human Arteriolar Vasodilation. Issue 1 (January 2021) - Hughes, William E.; Chabowski, Dawid S.; Ait-Aissa, Karima; Fetterman, Jessica L.; Hockenberry, Joseph; Beyer, Andreas M.; Gutterman, David D.
Abstract : Objective: Coronary artery disease (CAD) is associated with a compensatory switch in mechanism of flow-mediated dilation (FMD) from nitric oxide (NO) to H2 O2 . The underlying mechanism responsible for the pathological shift is not well understood, and recent reports directly implicate telomerase and indirectly support a role for autophagy. We hypothesize that autophagy is critical for shear stress–induced release of NO and is a crucial component of for the pathway by which telomerase regulates FMD. Approach and Results: Human left ventricular, atrial, and adipose resistance arterioles were collected for videomicroscopy and immunoblotting. FMD and autophagic flux were measured in arterioles treated with autophagy modulators alone, and in tandem with telomerase-activity modulators. LC3B II/I was higher in left ventricular tissue from patients with CAD compared with non-CAD (2.8±0.2 versus 1.0±0.2-fold change; P <0.05), although p62 was similar between groups. Shear stress increased Lysotracker fluorescence in non-CAD arterioles, with no effect in CAD arterioles. Inhibition of autophagy in non-CAD arterioles induced a switch from NO to H2 O2, while activation of autophagy restored NO-mediated vasodilation in CAD arterioles. In the presence of an autophagy activator, telomerase inhibitor prevented the expected switch (Control: 82±4%; NG-Nitro-l-arginine methyl ester: 36±5%; polyethylene glycol catalase: 80±3). Telomerase activation was unable to restore NO-mediated FMD in the presence of autophagy inhibition in CAD arterioles (control: 72±7%; NG-Nitro-l-arginine methyl ester: 79±7%; polyethylene glycol catalase: 38±9%). Conclusions: We provide novel evidence that autophagy is responsible for the pathological switch in dilator mechanism in CAD arterioles, demonstrating that autophagy acts downstream of telomerase as a common denominator in determining the mechanism of FMD. Abstract : Supplemental Digital Content is available in the text.